A hypervariable intron of the STAYGREEN locus provides excellent discrimination among Pisum fulvum accessions and reveals evidence for a relatively recent hybridization event with Pisum sativum - Weeden, N. F.; Lavin, M.; Abbo, S.; Coyne, C. J.; McPhee, K. (Frontiers in Plant Science, 2023)
An analysis of 82 non-synonymous Pisum fulvum accessions for sequence variation in a fragment of the STAYGREEN (SGR) locus revealed 57 alleles, most of which differed in indel structure. Eight additional P. fulvum accessions, each supposedly synonymous with a different accession of the initial group, were also analyzed. In every case the paired synonymous accessions possessed the same SGR sequence but varied slightly for a 6-trait morphological phenotype, indicating that SGR sequence is a much more reliable indicator of accession identity than is a morphological characterization. SGR sequence analysis confirmed our previous finding that P. fulvum accessions separate into two allele groups. This division was not supported by results of previous studies that were based on sequences distributed across the entire genome, suggesting that the division may have been produced by selection at a nearby locus and that the SGR phylogeny may not be good indicator of overall relationships within the species. One P. fulvum accession, PI 595941 (=JI1796), displayed an SGR sequence outside the variation typical of the species. Instead, its allele resembled alleles limited to a set of Pisum sativum landraces from the Middle East, suggesting hybridization between ancestors of PI 595941 and some primitive form of domesticated P. sativum. With one exception from the extreme northwest corner of Israel, P. fulvum accessions collected north of latitude 35.5o N were fixed for alleles from group A. These northern accessions also displayed greatly reduced SGR sequence diversity compared to group A accessions collected from other regions, suggesting that the northern populations may represent recent extensions of the range of the species. Group B accessions were distributed from Lake Tiberias south and were generally sympatric with the southern group A accessions. Although group B accessions occupied a smaller area than group A, the SGR sequence diversity in this group (28 alleles in 33 accessions) exceeded that for group A.